Physical parameters of RR Lyrae stars in M15 - García Lugo, G.; Arellano Ferro, H.; Rosenzweig, Patricia (Ciencia)
The V, R light curves for 33 RR Lyrae stars in M15 were used to calculate their physical parameters. The Blazhko effect, previously reported in V12, was not detected. The values for the iron content and distance of the cluster are: [Fe/H]= -1.98 Ó 0.24 and d = 8.67 Ó 0.41 kpc, respectively. The mean values of the physical parameters, determined for the RR Lyrae, stars place the cluster precisely into the sequences Oosterhoff type ”“ metallicity and metallicity ”“ effective temperature, valid for globular clusters. Evidences of evolution from the ZAHB are found for the RRc but not for the RRab stars.